Molecular identification and antibiotic resistance profiling of Salmonella species isolated from chickens in eastern Turkey - Arkali, Aydogan; Cetinkaya, Burhan (Bmc, 2020)
Background The aim of this study was to obtain quantitative data about the frequency, genotypic characterization and antibiotic resistance profiling ofSalmonellaagents in chicken flocks located in eastern Turkey. Results Feces samples representing at least 20% of the flock area were collected via sock swabs from commercial poultry flocks in the study region in addition to internal organs (liver, spleen, intestine) collected at necropsy of suspected chickens belonging to small family enterprises. The samples were analyzed by conventional bacteriological methods (ISO 6579:2002/A1:2007) for isolation, and genus specific (invA) PCR for the identification ofSalmonellaspp. Then, two mPCR were set up to determineSalmonellaserotypes and genotypic resistance status of the field isolates against ampicillin, tetracycline, trimethoprim-sulfamethoxazole and chloramphenicol antibiotics. In the PCR analysis of the suspected colonies, 98.5% were confirmed asSalmonellaspp., and, the most prevalent serotype was identified asS. Infantis with the proportion of 26.6% (17/64), followed byS.Enteritidis with 21.9% (14/64) andS.Typhimurium with 9.4% (6/64). The findings related to antibiotic resistance genes revealed that the most frequently determined gene wassul1with approximately 58%, while theblaTEMgene was detected at the lowest proportion with 20%, amongSalmonellaisolates. Conclusions The results indicated thatSalmonellainfections constitute a potential risk for chicken flocks in the country and that genotypic resistance rates against various antibiotics should draw particular attention in terms of both human and animal health.
Keywords: Salmonella; Chicken; mPCR characterization; Antibiotic resistance profiling